Comparative analysis of the therapeutic effect of antibiotic bone cement on Wagner grade 3 or 4 diabetic foot ulcer in heel and non-heel areas: a retrospective cohort study - Jian, Yang; Li, Li; Chen, Wei; An, Wenyu; Guan, Runxue; Zhang, Yanji; Wei, Jiarui; Chang, Shusen; Zhou, Jian; Nie, Kaiyu; Deng, Chengliang; Wei, Zairong (Frontiers in Endocrinology, 2025)
BackgroundHeel diabetic foot ulcers (hDFU) represent a particularly severe form of DFU, characterized by prolonged healing times and a significantly elevated risk of major amputation. Effective strategies to control infection and improve outcomes in this high-risk population are urgently needed. While antibiotic bone cement (ABC) has emerged as a promising therapy for general DFU, its specific efficacy for hDFU remains unverified. This study aims to evaluate the clinical efficacy of ABC-based management for hDFU compared to non-heel DFU (nhDFU) and to identify risk factors for major amputation.MethodsWe conducted a retrospective cohort study of 77 patients with severe (Wagner grade 3 or 4) DFUs treated with an ABC protocol. Patients were stratified into hDFU (n=35) and nhDFU (n=42) groups. Propensity score matching (PSM) was used to balance baseline characteristics. Outcomes included major amputation rates, length of stay (LOS), infection control [measured by white blood cell (WBC) count], and risk factors analyzed via modified Poisson regression.ResultsAt baseline, the hDFU group presented with greater disease severity, evidenced by significantly lower albumin levels (29.56 ± 6.45 g/L vs. 32.49 ± 5.25 g/L, P = 0.03) and higher WBC counts (Median: 14.86 vs. 10.32 × 109/L, P = 0.002). After PSM, the major amputation rate was not significantly different between the hDFU and nhDFU groups (12% vs. 8%, P = 1.0). ABC treatment significantly reduced WBC counts in both groups (P< 0.01), indicating effective infection control. Multivariate analysis identified alcohol abuse as an independent risk factor for major amputation both before [RR = 1.095, 95% confidence interval (CI): 1.011-1.186] and after PSM (RR = 1.123, 95% CI: 1.017-1.240). Hypoalbuminemia was also associated with increased amputation risk.ConclusionAn ABC-based management strategy is effective for severe hDFU, demonstrating comparable major amputation rates to nhDFU despite more severe initial presentations. It facilitates infection control and may contribute to shortened hospitalization. Clinicians should address modifiable risk factors, particularly alcohol abuse and hypoalbuminemia, to further improve limb salvage outcomes.